Book Information. Human Values in Education, Rudolf Steiner, Anthroposophic Press. London. (2004). $22.72, Pages 198. ISBN: 0-88010-544-5. - Agustinus Tampubolon; Muhammad Adha; Eska Prawisudawati Ulpa (Jurnal Ilmiah Mimbar Demokrasi, 2022)
Symptoms or behaviors called symptomatic by Steiner (2004) explain how interactions in the classroom only look at the physical presence around teachers and students. However actually, intrinsic value is very crucial to prioritize. The intrinsic value in students who need to be touched is their heart and soul to get to know each other better. Teaching classically with the view that the existence and readiness of students are the same is a way of thinking that should be addressed to present an unpretentious "open classroom climate" filled with love, care, and togetherness.